1971
DOI: 10.1001/archpedi.1971.02110010078013
|View full text |Cite
|
Sign up to set email alerts
|

Imipramine Pamoate in the Treatment of Childhood Enuresis

Abstract: Imipramine pamoate suspension was administered orally to 57 healthy children in a double-blind crossover design study with dosage sequence randomized to determine whether 10 or 25 mg daily would be more effective in controlling nocturnal enuresis, when compared to treatment with a placebo. Both dosage levels of imipramine produced a statistically significant decrease in the number of wet nights when compared to placebo therapy (P<0.01). After the double-blind trial, imipramine treatment was continued in 18 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1972
1972
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(5 citation statements)
references
References 33 publications
(2 reference statements)
1
4
0
Order By: Relevance
“…This result is also supported by several other studies where they found imipramine cured patients with primary enuresis during treatment period and after discontinuation of therapy it cause relapse in significant cases [19][20][21].…”
Section: Discussionsupporting
confidence: 85%
“…This result is also supported by several other studies where they found imipramine cured patients with primary enuresis during treatment period and after discontinuation of therapy it cause relapse in significant cases [19][20][21].…”
Section: Discussionsupporting
confidence: 85%
“…The old tricyclic antidepressant imipramine has in numerous studies proven to be superior to placebo in the treatment of unselected children with nocturnal enuresis [12][13][14][15]. For several decades, it was more or less the drug of choice and was widely prescribed all over the world.…”
Section: Introductionmentioning
confidence: 99%
“…This was probably a result of reports of their value in the treatment of this condition (Epstein and Guilfoyle, 1965;Kardash et al, 1968;Esperanca and Gerrard, 1969;Martin, 1971;Fraser, 1972;Kolvin et al, 1972). In our series however, parents seemed quite unaware of the potential dangers of these drugs.…”
Section: Discussionmentioning
confidence: 61%